Conductive silver paste with adjustable dielectric property and corrosion resistance and preparation method thereof

By modifying silver powder and other components in the conductive silver paste, conductive silver paste with adjustable dielectric characteristics and corrosion resistance is prepared, which solves the problem of irregulating dielectric characteristics and insufficient corrosion resistance of traditional conductive silver paste, and achieves high conductivity and long-term stability.

CN119852003APending Publication Date: 2025-04-18ANHUI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054185.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The dielectric characteristics of traditional conductive silver paste are unadjustable and have insufficient corrosion resistance, making it difficult to meet the needs of high-frequency performance and long-term stability.

Method used

A filler composed of silver powder, carbon nanotubes and coupling agents is used to modify silver powder, combined with organic solvents of isopropyl alcohol and ethylene glycol monomethyl ether, acrylic resin and other components, and a conductive silver paste with adjustable dielectric properties and corrosion resistance is prepared by ball milling.

Benefits of technology

The conductive network structure of silver paste is significantly optimized, the conductive performance and dielectric regulation capabilities are improved, the oxidation and corrosion resistance are enhanced, and the long-term stability in high humidity and corrosive environments are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005240880060000011
    Figure HDA0005240880060000011
  • Figure HDA0005240880060000012
    Figure HDA0005240880060000012
  • Figure HDA0005240880060000021
    Figure HDA0005240880060000021
Patent Text Reader

Abstract

The invention discloses conductive silver paste with adjustable dielectric property and corrosion resistance and a preparation method thereof. The conductive silver paste is prepared from the following raw materials in parts by weight: 50-70 parts of filler, 15-30 parts of binder, 10-20 parts of organic solvent, 1-3 parts of active agent, 0.5-1 part of dispersing agent and 1-3 parts of assistant, wherein the filler is prepared from silver powder, carbon nano tube and coupling agent modified silver powder. The conductive silver paste provided by the invention has high conductivity, adjustable dielectric property and excellent corrosion resistance, and is particularly suitable for various scenes such as flexible electronic equipment, high-frequency communication devices, printed circuits and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of conductive silver paste, and in particular to a conductive silver paste having both adjustable dielectric properties and corrosion resistance and a preparation method thereof, which is suitable for the fields of high-performance electronic devices, flexible electronics, radio frequency components, etc. Background Art

[0002] Traditional conductive silver paste has been widely used in the electronics industry due to its high conductivity and excellent mechanical properties. However, the conductive silver paste in the prior art still has the following significant deficiencies: the dielectric properties are not adjustable. The existing conductive silver paste pays more attention to the optimization of conductivity, lacks the systematic design and control of the dielectric properties, and it is difficult to achieve effective regulation of the dielectric constant and dielectric loss, which limits its application in different electromagnetic environments, especially in fields with strict requirements for high-frequency performance. Insufficient corrosion resistance. In high humidity or corrosive environments, the silver powder particles of traditional conductive silver paste are easily degraded due to oxidation or reaction with chemical substances. The destruction of the conductive network not only significantly reduces the conductive performance, but also greatly shortens the service life of electronic devices, making it difficult to meet the demand for long-term stability. These problems restrict its further development in the field of high-performance electronic devices. Summary of the invention

[0003] Based on the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a conductive silver paste having both adjustable dielectric properties and corrosion resistance and a preparation method thereof, while improving its conductivity and long-term stability.

[0004] To achieve the purpose, the present invention adopts the following technical solution:

[0005] The invention firstly discloses a conductive silver paste with adjustable dielectric properties and corrosion resistance. The raw materials of the conductive silver paste are composed of 50-70 parts of filler, 15-30 parts of binder, 10-20 parts of organic solvent, 1-3 parts of active agent, 0.5-1 part of dispersant and 1-3 parts of auxiliary agent in terms of weight. The filler is composed of silver powder, carbon nanotubes and silver powder modified by a coupling agent.

[0006] Furthermore, in the filler, the mass percentage of carbon nanotubes is 2-4%, and the mass ratio of coupling agent modified silver powder to silver powder is 1:0.5-2.

[0007] Furthermore, the coupling agent modified silver powder is prepared by mixing silver powder and silane coupling agent KH570 in a mixture of ethanol and water (the volume ratio of the two is 1:5), heating and stirring at 50-70°C for 2-4 hours, and then filtering and washing with ethanol and drying at 60-80°C. The mass of the silane coupling agent KH570 is 1%-3% of the mass of the silver powder.

[0008] Further, the organic solvent is a mixture of isopropanol and ethylene glycol monomethyl ether. Compared with a single or other mixed solvent (such as dimethyl succinate, dimethyl glutarate, N-methyl pyrrolidone, butyl acetate, terpineol, diethylene glycol butyl ether acetate, etc.), the mixture of isopropanol and ethylene glycol monomethyl ether can better disperse fillers, especially carbon nanotubes, and can also improve the conductive properties of silver paste.

[0009] Furthermore, the binder is at least one of acrylic resin, polymethyl methacrylate, polyurethane resin, epoxy resin and phenolic resin.

[0010] Furthermore, the dispersant is at least one of BYK-163, BYK-161, BYK-190, BYK-9076 and BYK-2510.

[0011] Furthermore, the active agent is at least one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate and nonylphenol polyoxyethylene ether. Modifying the carbon nanotubes with the active agent can improve the dispersibility of the carbon nanotubes and prevent them from agglomerating.

[0012] Furthermore, the auxiliary agent includes an anti-settling thixotropic agent and a defoaming agent; the anti-settling thixotropic agent is at least one of carboxymethyl cellulose, polyamide wax, organic bentonite and fumed silica; the defoaming agent is at least one of BYK-066N and an organosilicon defoaming agent.

[0013] The present invention also provides a method for preparing the conductive silver paste having both adjustable dielectric properties and corrosion resistance, comprising the following steps:

[0014] S1: adding carbon nanotubes to part of the organic solvent, then adding an activator, stirring thoroughly with a homogenizer, and then dispersing evenly with ultrasound to obtain an activated carbon nanotube dispersion;

[0015] S2: After the coupling agent modified silver powder, activated carbon nanotube dispersion, remaining organic solvent and binder are mixed and dispersed uniformly by ultrasonication, they are poured into a ball milling jar, and then silver powder, dispersant and additives are added for ball milling to obtain a conductive silver paste with adjustable dielectric properties and corrosion resistance. The speed of the ball mill is 400r / min~600r / min, and the ball milling time is 4h.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] 1. The conductive silver paste provided by the present invention is composed of a conductive filler, a binder and an organic additive, wherein the conductive filler includes conventional silver powder, carbon nanotubes and coupling agent modified silver powder. Carbon nanotubes, as a high aspect ratio conductive reinforcing material, significantly optimize the conductive network structure of the silver paste, improve the conductive performance, and give the material excellent dielectric regulation ability, so that it can meet the requirements of different application scenarios for dielectric properties. At the same time, the silver powder is surface modified by KH570 (γ-methacryloxypropyltrimethoxysilane) to form a dense silicone protective layer, which not only significantly improves the anti-oxidation and corrosion resistance of the silver paste, ensures the long-term stability of the silver paste in high humidity and corrosive environments, but also enhances the interfacial bonding between the silver powder and the substrate, and optimizes the dispersibility of the slurry.

[0018] 2. The present invention successfully constructs a multiphase composite system with high conductivity, adjustable dielectric properties and excellent corrosion resistance by optimizing the ratio of silver powder, carbon nanotubes, coupling agent-modified silver powder and other components. It is particularly suitable for flexible electronic devices, high-frequency communication devices, printed circuits and other scenarios. The obtained silver paste can still show excellent silver migration resistance and stable dielectric properties under high temperature and high humidity power-on conditions, further broadening the application field.

[0019] 3. The silver paste of the present invention combines dielectric property regulation with anti-corrosion design in a breakthrough way, providing an innovative solution with both high performance and versatility for the field of flexible electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The resistivity diagram of the conductive silver paste obtained in each embodiment and comparative example;

[0021] Figure 2 The conductive silver paste obtained in each embodiment and comparative example is 10 3 -10 7 Dielectric constant diagram in Hz;

[0022] Figure 3 The conductive silver paste obtained in each embodiment and comparative example is 10 3 -10 7 Hz dielectric loss average value graph;

[0023] Figure 4 The polarization curves of the conductive silver pastes obtained in the embodiments and comparative examples are shown in FIG.

[0024] Figure 5 Graph showing the silver migration test results of the silver pastes obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments improved or modified by ordinary technicians in this field belong to the scope of protection of the present invention. It should be understood that the embodiments of the present invention are only used to illustrate the technical achievements of the present invention, rather than to limit the scope of protection of the present invention. In the embodiments, the methods used are conventional methods unless otherwise specified.

[0026] Example 1

[0027] The present embodiment provides a conductive silver paste having both adjustable dielectric properties and corrosion resistance, wherein the raw materials are composed of: 30 parts of conventional nano silver powder, 1.5 parts of carbon nanotubes, 30 parts of coupling agent modified silver powder; 15 parts of an organic solvent composed of isopropyl alcohol and ethylene glycol monomethyl ether in a mass ratio of 2:3, 15 parts of a binder composed of an epoxy resin and its corresponding curing agent and accelerator, 2 parts of an activator composed of polyvinyl pyrrolidone and nonylphenol polyoxyethylene ether in a mass ratio of 1:2, 0.5 parts of a dispersant BYK-163, 1 part of an organic silicone defoamer and 1 part of an anti-settling thixotropic agent polyamide wax.

[0028] The configuration method of the conductive silver paste in this embodiment is:

[0029] S1: Add carbon nanotubes to an appropriate amount of organic solvent, then add an activator, stir thoroughly with a homogenizer (500 rpm, 10 min), and then disperse ultrasonically for 20 min to obtain an activated carbon nanotube dispersion.

[0030] S2: After mixing nano silver powder and silane coupling agent KH570 in a mixture of ethanol and water (the volume ratio of the two is 1:5), heating and stirring at 60°C for reaction for 3 hours, then filtering and washing with ethanol and drying at 70°C to obtain coupling agent modified silver powder, the mass of silane coupling agent KH570 is 2% of the mass of silver powder.

[0031] S3: After the coupling agent modified silver powder, activated carbon nanotube dispersion, remaining organic solvent and binder are mixed and dispersed uniformly by ultrasonication, they are poured into a ball mill, and then silver powder, dispersant and additives are added for ball milling to obtain a conductive silver paste with adjustable dielectric properties and corrosion resistance. The speed of the ball mill is 500r / min, and the ball milling time is 4h.

[0032] Example 2

[0033] The raw materials of the conductive silver paste provided in this embodiment are different from those in Embodiment 1 only in that the filler includes 30 parts of conventional nano silver powder, 2 parts of carbon nanotubes, and 30 parts of coupling agent modified silver powder.

[0034] The configuration method of the conductive silver paste in this embodiment is the same as that in the first embodiment.

[0035] Example 3

[0036] The raw materials of the conductive silver paste provided in this embodiment are different from those in Embodiment 1 only in that the filler includes 30 parts of conventional nano silver powder, 2.5 parts of carbon nanotubes, and 30 parts of coupling agent-modified silver powder.

[0037] The configuration method of the conductive silver paste in this embodiment is the same as that in the first embodiment.

[0038] Example 4

[0039] The raw materials of the conductive silver paste provided in this embodiment differ from those in Embodiment 1 only in that the filler includes 40 parts of conventional nano silver powder, 2 parts of carbon nanotubes, and 20 parts of coupling agent-modified silver powder.

[0040] The configuration method of the conductive silver paste in this embodiment is the same as that in the first embodiment.

[0041] Example 5

[0042] The raw materials of the conductive silver paste provided in this embodiment are different from those in Embodiment 1 only in that the filler includes 20 parts of conventional nano silver powder, 2 parts of carbon nanotubes, and 40 parts of coupling agent modified silver powder.

[0043] The configuration method of the conductive silver paste in this embodiment is the same as that in the first embodiment.

[0044] Comparative Example 1

[0045] The raw materials of the conductive silver paste provided in this comparative example are different from those in Example 1 only in that the filler is 60 parts of conventional nano silver powder.

[0046] Comparative Example 2

[0047] The raw materials of the conductive silver paste provided in this comparative example are different from those in Example 1 only in that the filler includes 30 parts of conventional nano silver powder, 0 parts of carbon nanotubes, and 30 parts of coupling agent-modified silver powder.

[0048] The resistance of the silver paste obtained in the above embodiments and comparative examples was tested as follows: the paste was coated on the PET film substrate using a scraper, placed in an oven at 135°C for drying and curing, and the film size was fixed to 5 cm×5 cm. A four-probe tester was used, the equipment test mode was adjusted to resistivity test, the probes were placed vertically on the film surface, multiple tests were performed, the average value was taken, and the value was recorded.

[0049] The polarization curve test of each embodiment and comparative example was carried out as follows: the slurry was coated on the center of the tinplate substrate with a scraper, placed in an oven at 135°C for drying and curing, sealed with a sealant, and a 1cm×1cm working area was exposed to serve as a working electrode. The polarization curve test of the coating sprayed on the tinplate was carried out by an electrochemical workstation using a platinum wire electrode as a counter electrode, a calomel electrode as a reference electrode, and a 3.5% sodium chloride solution as an electrolyte.

[0050] The dielectric properties of the silver paste obtained in the above embodiments and comparative examples were tested as follows: the silver paste was made into a circular shape with a diameter of 20 mm and a thickness of 1 mm, placed in an oven for drying and curing at 135°C, and a frequency scanning test was performed within a certain frequency range using a broadband dielectric impedance spectrometer (BDS).

[0051] The silver paste migration diagrams obtained in Example 1 and Comparative Example 1 were tested as follows: silver paste was filled into the pre-prepared grooves, and a stable DC bias voltage was applied to the grooves. A few drops of pure water were dripped into the middle area of ​​the grooves to simulate the environmental moisture under high humidity conditions, and the effect of the electric field on the migration activity of silver particles under high humidity conditions was observed. After 10 minutes of power-on operation, the silver migration of the silver paste filled in the grooves was observed using a polarizing microscope.

[0052] Figure 1 It can be seen from the resistivity graph that compared with Comparative Example 2, as the amount of carbon nanotubes added in Examples 1, 2, and 3 increases, the resistivity of the silver paste gradually decreases. This is because the carbon nanotubes form a bridging effect between the silver particles, thereby building a more continuous and denser conductive network, which can significantly reduce the contact resistance between the fillers, thereby reducing the overall resistivity. Compared with Example 4, the resistivity of the silver paste obtained in Examples 2 and 5 is lower. This is because KH570 combines with the surface of the silver powder through chemical bonding to form a stable molecular layer, which not only significantly improves the dispersibility of the silver powder, but also enhances the interfacial compatibility between the silver powder particles. The modified silver powder can form a more uniform and compact conductive network, thereby reducing the resistivity.

[0053] from Figure 2 It can be seen from the dielectric constant graph that in Comparative Example 2 and Examples 1, 2, and 3, as the carbon nanotube content increases, the overall dielectric constant of the silver paste shows a trend of gradual increase. This is because as the amount of carbon nanotubes added increases, the carbon nanotubes gradually approach each other, a conductive network begins to form, and more space charges are introduced into the silver paste. The charges gather at the interface between the carbon nanotubes and the substrate, resulting in interface polarization, thereby increasing the dielectric constant.

[0054] from Figure 3It can be seen from the average dielectric loss value that compared with the silver paste without adding carbon nanotubes in Comparative Example 2, with the addition of carbon nanotubes in Examples 1, 2, and 3, the dielectric loss of the silver paste is significantly reduced. This is because carbon nanotubes improve the filler interface, inhibit leakage current, reduce polarization loss, and optimize the structure of the composite material in multiple ways, so that the silver paste can significantly reduce the loss while maintaining a high dielectric constant. This feature also meets the requirements for low loss and stable performance in high-frequency devices.

[0055] from Figure 4 It can be seen from the polarization curve that the silver paste obtained in Example 2 and Example 5 is more corrosion-resistant than the silver paste obtained in Example 4. This is because the surface energy of the unmodified silver powder is relatively high, and it is easy to react with the corrosive medium, resulting in corrosion of the silver powder surface. KH570, as a silane coupling agent, can form a stable chemical bond with the surface of the silver powder, forming a uniform protective layer, which effectively prevents the corrosive medium from contacting the surface of the silver powder, thereby significantly improving the corrosion resistance of the silver powder. In addition, the interface between the unmodified silver powder particles is mainly formed through physical contact, and the interface compatibility is poor. It is easy for the corrosive medium to penetrate into the silver powder particles, resulting in corrosion of the silver powder. The silver powder particles modified by KH570 form chemical bonds, and the interface compatibility is significantly improved, which reduces the penetration path of the corrosive medium, making the overall structure of the silver paste more stable, thereby improving the corrosion resistance.

[0056] from Figure 5 It can be seen from the silver migration diagram that in Comparative Example 1, the silver migration phenomenon is very serious, forming an obvious dense dendritic structure, which can easily cause the silver paste in the grooves on both sides to migrate and interconnect, thereby causing the product to short-circuit and fail. In contrast, the silver paste of Example 1 basically eliminates the silver migration phenomenon. This is because the surface of the silver particles is modified by the coupling agent to form a stable organic silane coating, which reduces its migration tendency under the action of the electric field, thereby effectively inhibiting the occurrence of silver migration.

[0057] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A conductive silver paste having both adjustable dielectric properties and corrosion resistance, characterized in that: The raw materials are composed of 50-70 parts of filler, 15-30 parts of binder, 10-20 parts of organic solvent, 1-3 parts of active agent, 0.5-1 part of dispersant and 1-3 parts of auxiliary agent in terms of weight. The filler is composed of silver powder, carbon nanotubes and silver powder modified by coupling agent.

2. The conductive silver paste having both adjustable dielectric properties and corrosion resistance according to claim 1, characterized in that: In the filler, the mass percentage of carbon nanotubes is 2-4%, and the mass ratio of coupling agent modified silver powder to silver powder is 1:0.5-2.

3. The conductive silver paste having both adjustable dielectric properties and corrosion resistance according to claim 1, characterized in that: The coupling agent modified silver powder is prepared by mixing silver powder and silane coupling agent KH570 in a mixture of ethanol and water, heating and stirring for reaction, and then filtering, washing and drying with ethanol. The mass of the silane coupling agent KH570 is 1%-3% of the mass of the silver powder.

4. The conductive silver paste having both adjustable dielectric properties and corrosion resistance according to claim 3, characterized in that: The temperature of the heating and stirring reaction is 50-70° C. and the time is 2-4 hours.

5. The conductive silver paste having both adjustable dielectric properties and corrosion resistance according to claim 1, characterized in that: The organic solvent is a mixture of isopropanol and ethylene glycol monomethyl ether.

6. The conductive silver paste with adjustable dielectric properties and corrosion resistance according to claim 1, characterized in that: The binder is at least one of acrylic resin, polymethyl methacrylate, polyurethane resin, epoxy resin and phenolic resin.

7. The conductive silver paste having both adjustable dielectric properties and corrosion resistance according to claim 1, characterized in that: The dispersant is at least one of BYK-163, BYK-161, BYK-190, BYK-9076 and BYK-2510.

8. The conductive silver paste with adjustable dielectric properties and corrosion resistance according to claim 1, characterized in that: The active agent is at least one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate and nonylphenol polyoxyethylene ether.

9. The conductive silver paste with adjustable dielectric properties and corrosion resistance according to claim 1, characterized in that: The auxiliary agent includes an anti-settling thixotropic agent and a defoaming agent; the anti-settling thixotropic agent is at least one of carboxymethyl cellulose, polyamide wax, organic bentonite and fumed silica; the defoaming agent is at least one of BYK-066N and an organic silicon defoaming agent.

10. A method for preparing a conductive silver paste having both adjustable dielectric properties and corrosion resistance as claimed in any one of claims 1 to 9, characterized in that: The steps include: S1: adding carbon nanotubes to part of the organic solvent, then adding an activator, stirring thoroughly with a homogenizer, and then dispersing evenly with ultrasound to obtain an activated carbon nanotube dispersion; S2: The coupling agent modified silver powder, activated carbon nanotube dispersion, remaining organic solvent and binder are mixed and dispersed uniformly by ultrasonication, then poured into a ball mill, and silver powder, dispersant and additives are added and ball milled to obtain a conductive silver paste with adjustable dielectric properties and corrosion resistance.